(untitled) (Fiep Bulletin - online, 2014)
The present study it had as objective to analyze through statistical data the influence of the Labor Recreation in the perception of the pupils in relation the possible modifications in the physical context for accomplishment of the daily tasks of work, being aimed at improvements in the environment of work for the practical one of the modality. To leave of this an instrument structuralized for opened questions was elaborated and closed, divided in two phases, the first one destined the information that they preceded the introduction of the practical one of the Labor Recreation in the organization, with seven questions and the second to the ending of the program in the organization with sixteen questions, that had registered the occurrences with 36 individuals, in the understood etária band enter the 19 48 years of both the sorts, being the restricted research the workers of an engineering organization, situated in the Zone South of the City of Rio De Janeiro, that possess a turn of eight daily hours and that they basically work in computers in its greater part of the horária load, credited for analysis statistics (COAST GRANDSON, 1995). after the conclusion of the study, evidenced that itens with relevance to the research had been: Considerable modifications in the work environment, increase in the disposal for the hours of working, in the concentration and the social integration and reduction in the anxiety. What it was presented in latent way with the conclusion, was the lack of reference to structuralize the study, what credited to this research the importance of an element auxiliary in future scientific productions, a time that the Labor activity comes each time more growing in the organizations.